Augmenting iron accumulation in cassava by the beneficial soil bacterium Bacillus subtilis (GBO3) - Freitas, Mônica A.; Medeiros, Flavio H. V.; Carvalho, Samuel P.; Guilherme, Luiz R. G.; Teixeira, William D.; Zhang, Huiming; Paré, Paul W. (Frontiers in Plant Science, 2015)
Cassava (Manihot esculenta), a major staple food in the developing world, provides a basic carbohydrate diet for over half a billion people living in the tropics. Despite the iron abundance in most soils, cassava provides insufficient iron for humans as the edible roots contain 3-12 times less iron than other traditional food crops such as wheat, maize, and rice. With the recent identification that the beneficial soil bacterium Bacillus subtilis (strain GB03) activates iron acquisition machinery to increase metal ion assimilation in Arabidopsis, the question arises as to whether this plant-growth promoting rhizobacterium (PGPR) also augments iron assimilation to increase endogenous iron levels in cassava. Biochemical analyses reveal that shoot-propagated cassava with GB03-inoculation exhibit elevated iron accumulation after 140 days of plant growth as determined by X-ray microanalysis and total foliar iron analysis. Growth promotion and increased photosynthetic efficiency were also observed for greenhouse-grown plants with GB03-exposure. These results demonstrate the potential of microbes to increase iron accumulation in an important agricultural crop and is consistent with idea that microbial signaling can regulate plant photosynthesis.